BASIC TENSE PROBLEMS OF THE FIRST SEMESTER STUDENTS OF ENGLISH LANGUAGE EDUCATION STUDY PROGRAM - Wahyuningtyas, Elisabeth Wulan; Bram, Barli (Sanata Dharma University Yogyakarta, 2018)
This paper investigated the problems of understanding basic or fundamental tenses in English grammar (the present tense, present continuous tense, present future tense, and present future continuous) that are faced by the first semester students of the English Language Education Study Program of Sanata Dharma University, Yogyakarta. Basic tenses in English grammar play a decisive role in various aspects related to learning English as the target language. Accordingly, it is essential to conduct a study on the issues of basic tenses in order to assist students to overcome their grammatical problems. Data were collected through questionnaires that were emailed to the participants. Results showed that the students had difficulties in producing or analyzing the present continuous tense, the present perfect tense and the present perfect continuous tense. The first semester students also faced difficulty in remembering the formula of each tense, admitting that they did not review the basic tenses regularly and the students found it difficult to comprehend their grammar lessons well in the classroom.Â DOI: https://doi.org/10.24071/ijiet.2018.020206